Evaluación del proceso constructivo de la chimenea de equilibrio del proyecto hidroeléctrico Minas - San Francisco y propuesta alternativa para optimizar tiempo de ejecución y costo de la obra. - Conza Herrera, Jarry Kerly (2015)
During the project implementation is always seeking to improve construction processes used, in order to leverage resources, to optimize time and cost in the construction of hydroelectric plants. It aims to assess the construction processes of the fireplace, to determine the most likely to provide us with greater viability, determined by the literature search and the method applied. The importance of this assessment is reflected in the reports generated during the construction processes of the surge hydroelectric project Minas-San Francisco, which will be a scientific and technical contribution significant, to be used as knowledge base in education centers superior, and it is of great importance to develop the profile of the professional future of civil engineering. In addition, this assessment has far-reaching implications for the development of future similar projects and can help solve practical problems that occur in the process of construction of similar works. With the results obtained knowledge that contributes to suggest ideas, recommendations, changes in the time of a study for the construction of fireplaces Balancing rojects Hydropower is generated. This assessment of the construction of the fireplace Balance to be part of the Hydroelectric Project Minas-San Francisco contributes to the commitment to generate. Factual information creating an instrument to collect and analyze data to define a concept or variable in order to suggest a suitable method to optimize the technical and economic resources of this type of civil works.